RUSSIA’S STRATEGIC COMMUNICATION IN THE CIS (2022–2024): NARRATIVES, TOOLS, AND REGIONAL RESPONSES POST-UKRAINE INVASION - Firdavs Azimqulov (Web of Journals Publishing, 2025)
Following its full-scale invasion of Ukraine in February 2022, Russia intensified its strategic communication efforts toward the Commonwealth of Independent States (CIS) to preserve regional influence amid growing geopolitical isolation. This paper investigates how the Kremlin constructed and disseminated narratives between 2022 and 2024 to shape perceptions. Drawing on Constructivist theory, the study emphasizes the role of identity, memory, and discourse in Russia’s foreign policy communication, focusing on tools such as state-backed media, official rhetoric, historical symbolism, and bilateral diplomatic engagement. The paper contributes to understanding how state-led communication operates as a tool of influence and how identity politics shapes regional responses in the post-Ukraine war context.